Distribusi Pasar Luar Negeri - Nasution, Muhammad Iqbal; Fachrezi, Harahap Adrie; Darma, Surya; Rahman, Dedy; Suhairi, Suhairi (LPPM Universitas Labuhanbatu, 2022)
This study aims to find out how the distribution of foreign markets. This research is a qualitative descriptive research that explains phenomena and data and previous research, then draws conclusions from the existing problems. The purpose of research using this method is to describe the problem taken more accurately and clearly based on facts. Data collection is secondary data with journals, news, and government announcements which are analyzed and explained in the discussion. The results of this study are basically, the target of international distribution (in a broad sense) is the same as in the domestic market, namely providing products according to the product items needed by buyers in the quantity, time and condition needed with the most efficient cost possible. This target can be achieved through the use of distribution channels and management activities for the physical distribution or logistics of the company's products. However, this target is more difficult to achieve, especially for global companies because of different economic developments in each country which will affect the existence of these institutions and distribution systems in each of these countries. Furthermore, this will have an impact on the distribution strategy and the costs incurred, the different consumer behaviors in each country, especially shopping behavior, differences in the distance between one country and another which will affect logistics costs and laws and regulations, especially related to the traffic flow of goods which may vary from one country to another.